KUALITAS PELAYANAN TK NEGERI BANGETAYU WETAN KECAMATAN GENUK KOTA SEMARANG - Siregar, Mery Apriana; Widowati, Nina (Journal of Public Policy and Management Review, 2018)
Kindergartens are institutions that are responsible for the implementation of Early Childhood Education kindergartens as the spearhead of Educational Implementation, are required to always improve the quality of service. Likewise with the Bangetayu Wetan Kindergarten in Genuk Sub-district, Semarang City as the education provider. The implementation of Bangetayu Wetan Kindergarten is still experiencing problems in the process of standardizing the implementation of kindergarten From the explanation above, the researcher wants to study: (1) Description of the quality of services of Bangetayu Wetan Kindergarten (2) aspects that support and hinder the quality of service of Bangetayu Wetan Kindergarten. Benefits taken from this study to provide information about the quality of Bangetayu Wetan kindergarten services and aspects that need to be considered in improving the service quality of Bangetayu Wetan Kindergarten. Using qualitative descriptive methods, it was found that the need for understanding of achievement and standardization was needed so that the formation and implementation of activities carried out by the kindergarten institutions became clear. Parents are quite satisfied with the services provided by Wetan because they get enough information and good interaction between parents and kindergarten institutions. Constraints occur in the lack of educators and lack of facilities and infrastructure. For this reason, support is needed from the government, especially in Facilities and Infrastructure to support kindergarten activities.